2013
DOI: 10.13005/ojc/290255
|View full text |Cite
|
Sign up to set email alerts
|

Study of Antioxidant Activity of Juglans regia leaves

Abstract: Free radicals are linked with the majority of diseases and the partially reduced metabolites of oxygen and nitrogen, are highly toxic and reactive 1-2. Oxidation is one of the most important route for producing free radicals in food, drugs and living systems. Antioxidants are the substances that when present in low concentration significantly delay or reduce the oxidation of the substrate. Antioxidants protect the living systems from damaging oxidation reactions by reacting with free radicals 3. Juglans regia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Despite the fact that careful assignment of the characteristic UV, 1 H-and 13 C-magnetic resonance data can distinguish the two isomers, there are occasions when investigators have concluded wrongly about the structure of their isolates 29 . For instance, 7-O-β-D-glucopyranosyl-6-C-β-D-glucopyranosylapigenin (saponarin) has been reported to occur in mature barley (Hordeum vulgare) leaves, along with lutonarin and its 3'-hydroxylated analogue [29][30][31] . A number of publications have described the structure of this glycoflavone, isolated from young green barley leaves, as 2"-O-β-Dglucopyranosyl-6-C-β-D-glucopyranosylapigenin (5) 32-…”
Section: Foliar Phenolics Of Cucumismentioning
confidence: 99%
“…Despite the fact that careful assignment of the characteristic UV, 1 H-and 13 C-magnetic resonance data can distinguish the two isomers, there are occasions when investigators have concluded wrongly about the structure of their isolates 29 . For instance, 7-O-β-D-glucopyranosyl-6-C-β-D-glucopyranosylapigenin (saponarin) has been reported to occur in mature barley (Hordeum vulgare) leaves, along with lutonarin and its 3'-hydroxylated analogue [29][30][31] . A number of publications have described the structure of this glycoflavone, isolated from young green barley leaves, as 2"-O-β-Dglucopyranosyl-6-C-β-D-glucopyranosylapigenin (5) 32-…”
Section: Foliar Phenolics Of Cucumismentioning
confidence: 99%